Effects of sorghum endosperm hardness and processing on growth performance and nutrient digestibility in pigs and broiler chicks - Cao, H.; Hines, Robert H.; Park, J.S.; Senne, B.W.; Jiang, J.M.; Froetschner, J.R.; Sorrell, P.; Hancock, Joe D.; Behnke, Keith C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
In nursery pigs, the greatest digestibilities of DM, N, and OE were observed with soft sorghum. In finishing pigs, no difference was observed in digestibility of nutrients among the sorghum genotypes. Chicks fed soft sorghum had better F/G than chicks fed medium and hard sorghum. Finally, thermal processing (steam flaking and extrusion) improved ADG and F/G and digestibilities of DM, N, and GE compared to grinding (coarse and fine).
Keywords: Swine; Sorghum; Extrusion; Steam flaking; Digestibility